Integration of CpG-free DNA induces de novo methylation of CpG islands in pluripotent stem cells - Takahashi, Yuta; Wu, Jun; Suzuki, Keiichiro; Martinez-Redondo, Paloma; Li, Mo; Liao, Hsin-Kai; Wu, Min-Zu; Hernández-Benítez, Reyna; Hishida, Tomoaki; Shokhirev, Maxim Nikolaievich; Esteban, Concepcion Rodriguez; Sancho-Martinez, Ignacio; et al. (Science (American Association for the Advancement of Science), 2017)
CpG islands (CGIs) are primarily promoter-associated genomic regions and are mostly unmethylated within highly methylated mammalian genomes. The mechanisms by which CGIs are protected from de novo methylation remain elusive. Here we show that insertion of CpG-free DNA into targeted CGIs induces de novo methylation of the entire CGI in human pluripotent stem cells (PSCs). The methylation status is stably maintained even after CpG-free DNA removal, extensive passaging, and differentiation. By targeting the DNA mismatch repair gene MLH1 CGI, we could generate a PSC model of a cancer-related epimutation. Furthermore, we successfully corrected aberrant imprinting in induced PSCs derived from an Angelman syndrome patient. Our results provide insights into how CpG-free DNA induces de novo CGI methylation and broaden the application of targeted epigenome editing for a better understanding of human development and disease.